2023
DOI: 10.1136/bmjsrh-2023-201792
|View full text |Cite
|
Sign up to set email alerts
|

Risk of thromboembolism in patients with COVID-19 who are using hormonal contraception: a Cochrane systematic review

Abstract: BackgroundThe coronavirus disease COVID-19 is associated with an increased risk of thrombotic events. Individuals with COVID-19 using hormonal contraception could be at additional risk for thromboembolism, but evidence is sparse.MethodsWe conducted a systematic review on the risk of thromboembolism with hormonal contraception use in women aged 15–51 years with COVID-19. We searched multiple databases through March 2022, including all studies comparing outcomes of patients with COVID-19 using or not using hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…At present, there is no consensus regarding the optimal management of ECT (i.e., whether to continue or hold) during significant infection, and recommendations are primarily based on expert opinion and clinical extrapolation. 23 Interestingly, epidemiologic data have shown that women have superior outcomes from COVID-19 infection compared to men, attributed in part to higher levels of estrogen and progesterone. 24 Both estrogen and progesterone are known to be potent immunomodulators and may play a role in mitigating the adverse effects associated with COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no consensus regarding the optimal management of ECT (i.e., whether to continue or hold) during significant infection, and recommendations are primarily based on expert opinion and clinical extrapolation. 23 Interestingly, epidemiologic data have shown that women have superior outcomes from COVID-19 infection compared to men, attributed in part to higher levels of estrogen and progesterone. 24 Both estrogen and progesterone are known to be potent immunomodulators and may play a role in mitigating the adverse effects associated with COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%